METAPHORICAL EXPRESSIONS USED IN EMILY DICKINSON’S POEMS - Tetema Telaumbanua (Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this research was to analyze the metaphorical expression used in Dickinson’s Poems and the function of the metaphor used. In analyzing the data, the researcher used the metaphor theory that was introduced by Newmark. Metaphor was divided into six types of metaphor they were dead metaphor, cliche metaphor, stock or standard metaphor, adapted metaphor, recent metaphor and original metaphor. The result of this reseach was done by researcher in documentation form in library. This research was descriptive qualitative research because the researcher applied the data in the term words and sentences. In analyzing the data the researcher applied the technique of data analysis they are data organizing, memoing, coding and Presenting. Conclusion could be drawn that from the ten choosen poems there are twelve metaphorical expression used by her that divided into four types from six types of metaphor they are dead metaphor, cliche metaphor, adapted metaphors and original metaphor. The researcher found that the meaning of metaphor in the choosen poems talk about life and sadness. The poems convey various message. There is social life message behind the poems. The researcher suggest in reading poem, it is important for students to understand more about metaphor, since understanding a poem cannot be separated in figurative language especially metaphor. It is emphasized that teacher has responsibility in explaining the metaphorical expression to the students in order to avoid the misinterpretation